Cholinergic excitation complements glutamate in coding visual information in retinal ganglion cells. (21st June 2018) - Sethuramanujam, Santhosh; Awatramani, Gautam B.; Slaughter, Malcolm M.
Abstract : Key points: Starburst amacrine cells release GABA and ACh. This study explores the coordinated function of starburst‐mediated cholinergic excitation and GABAergic inhibition to bistratified retinal ganglion cells, predominantly direction‐selective ganglion cells (DSGCs). In rat retina, under our recording conditions, starbursts were found to provide the major excitatory drive to a sub‐population of ganglion cells whose dendrites co‐stratify with starburst dendrites (putative DSGCs). In mouse retina, recordings from genetically identified DSGCs at physiological temperatures reveal that ACh inputs dominate the response to small spot‐high contrast light stimuli, with preferential addition of bipolar cell input shifting the balance towards glutamate for larger spot stimuli In addition, starbursts also appear to gate glutamatergic excitation to DSGCs by postsynaptic and possibly presynaptic inhibitory processes Abstract: Starburst amacrine cells release both GABA and ACh, allowing them to simultaneously mediate inhibition and excitation. However, the precise pre‐ and postsynaptic targets for ACh and GABA remain under intense investigation. Most previous studies have focused on starburst‐mediated postsynaptic GABAergic inhibition and its role in the formation of directional selectivity in ganglion cells. However, the significance of postsynaptic cholinergic excitation is only beginning to be appreciated. Here, we found that light‐evoked responses measured in bi‐stratified rat ganglion cells with dendrites that co‐fasciculate with ON and OFF starburst dendrites (putative direction‐selective ganglion cells, DSGCs) were abolished by the application of nicotinic receptor antagonists, suggesting ACh could act as the primary source of excitation. Recording from genetically labelled DSGCs in mouse retina at physiological temperatures revealed that cholinergic synaptic inputs dominated the excitation for high contrast stimuli only when the size of the stimulus was small. Canonical glutamatergic inputs mediated by bipolar cells were prominent when GABA/glycine receptors were blocked or when larger spot stimuli were utilized. In mouse DSGCs, bipolar cell excitation could also be unmasked through the activation of mGluR2, 3 receptors, which we show suppresses starburst output, suggesting that GABA from starbursts serves to inhibit bipolar cell signals in DSGCs. Taken together, these results suggest that starbursts amplify excitatory signals traversing the retina, endowing DSGCs with the ability to encode fine spatial information without compromising their ability to encode direction. Key points: Starburst amacrine cells release GABA and ACh. This study explores the coordinated function of starburst‐mediated cholinergic excitation and GABAergic inhibition to bistratified retinal ganglion cells, predominantly direction‐selective ganglion cells (DSGCs). In rat retina, under our recording conditions, starbursts were found to provide the major excitatory drive to a sub‐population of ganglion cells whose dendrites co‐stratify with starburst dendrites (putative DSGCs). In mouse retina, recordings from genetically identified DSGCs at physiological temperatures reveal that ACh inputs dominate the response to small spot‐high contrast light stimuli, with preferential addition of bipolar cell input shifting the balance towards glutamate for larger spot stimuli In addition, starbursts also appear to gate glutamatergic excitation to DSGCs by postsynaptic and possibly presynaptic inhibitory processes